Experiences of infertile women pursuing treatment in Kenya: a qualitative study - Anne Njogu; Julius Njogu; Albanus Mutisya; Yang Luo (BMC, 2022)
Abstract Background The infertility treatment process is associated with various psychological, physical, social, moral, and financial challenges, especially for women. The women are likely to report low marital satisfaction and emotional distress due to fertility treatment demands. This study explored how infertile women described their treatment experience and how they coped with treatment demands as they underwent treatment at three gynecology outpatient clinics in Kenya. Methods A qualitative phenomenological research design was used to analyze and describe women's fertility treatment experiences. The data were collected through semi-structured in-depth interviews with 33 infertile women selected purposively. Trustworthiness of the findings was ensured using Guba and Lincoln's criteria. The recorded interviews were transcribed verbatim and then analyzed using reflective thematic analysis, developed by Braun and Clarkes. Results Three themes and 13 sub-themes related to women's fertility treatment experiences and coping strategies were identified. The theme challenges encountered during fertility treatment have three sub-themes: emotional distressing, physical pain, and financial constraining. Theme impacts of fertility treatment on relationships have three sub-themes: relationship with their husband, relationship with their family, and relationship with their friends. Finally, coping with fertility treatment has six sub-themes: religious practices and personal faith, giving in to feelings, shifting focus, taking a break, staying with their relative's children, and receiving support from others. Conclusion The experiences of women undergoing treatment are multi-dimensional. Therefore, incorporating psychosocial interventions or counseling into the fertility treatment routine with National Health Insurance Fund cards may reduce the treatment burden, improving women's psychological well-being and relationships with their husbands, family, and friends.